Leaving the wild : the unnatural history of dogs, cats, cows, and horses - Ehringer, Gavin (Pegasus Books, 2017)
"The domestication of animals changed the course of human history. But what about the animals who abandoned their wild existence in exchange for our care and protection? Domestication has proven to be a wildly successful survival strategy. But this success has not been without its drawbacks. A modern dairy cow's daily energy output equals that of a Tour de France rider. Feral cats overpopulate urban areas. And our methods of breeding horses and dogs have resulted in debilitating and sometimes lethal genetic diseases. But these problems and more can be addressed, if we have the will and the compassion. Human values and choices determine an animal's lot in life even before he or she is born. Just as a sculptor's hands shape clay, so human values shape our animals' for good and or ill. The little-examined, yet omnipresent act of breeding lies at the core of Gavin Ehringer's eye-opening book. You'll meet cows cloned from steaks, a Quarter horse stallion valued at $7.5 million, Chinese dogs that glow in the dark, and visit a Denver cat show featuring naked cats and other cuddly mutants. Is this what the animals bargained for all those millennia ago, when they first joined us by the fire?"--Amazon.com.